Coconut Coir Experimental Process for Producing an Alternative Block Toy Compound - Bahari Mohd Yusoff, Saiful; Hamdan, Sinin; Ibrahim, Zalina; Jhihan Abdullah, Shah (International Journal of Engineering and Technology, 2018)
Currently, children’s block toys use solid wood, processed wood and Medium-Density Fiber board (MDF). MDF is a mixture of sawdust that is held together with wax, resin and formaldehyde and has been widely used to produce children’s toys. MDF are heavy and found to be health hazardous especially to children. This research focuses on the process of transforming the waste from the coconut coir/husk as an alternative to the current unsafe materials into toy block. The coconut coir/husk is creatively processed to produce children toy block that are soft, lightweight, cheap, harmless for children to use and environmental friendly. The process involved treatment of insignificant waste and transforming it into a competitive product, thus reducing mass pollution by the coconut farmers and open burning of coconut coir/husks.